Transport system and its impact on the sustainable development of the Russian economy - E. V. Zenkina; V. M. Kutovoi (Вестник университета)
The main advantage of Russia is its huge territory, and as a сonsequence its transit potential. All the shortest trade routes, connecting Asia and Europe, pass through the Russian territory. For sustainable economic development and strengthening of Russia’s influence, it is important to realize the transport potential of the region, in which Russia will occupy a key place as a transit country. To be a full-fledged participant in world trade, Russia needs a modern transport system. The problems of the current state of the transport system of Eurasia have been considered in the article, the ways to increase the quality and competitiveness of Russian transport have been adduced.